2016
DOI: 10.1007/978-3-319-46068-0_53
|View full text |Cite
|
Sign up to set email alerts
|

Academic Social Networks and Communication Researchers from Universities in the North of Portugal: An Analysis of Academia.edu and ResearchGate

Abstract: Abstract:Academic social networks emerge as an opportunity for researchers to improve their work and to potentially increase both the dissemination of their research and their collaboration with other scholars. However, there are still many gaps, uncertainties and reluctance surrounding academic social networks. This is not surprising, as they are a new phenomenon and are still not en a par with traditional media in terms of prestige and recognition. Considering such platforms as objects of study may contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
1
11
1
1
Order By: Relevance
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).…”
Section: Researchgatementioning
confidence: 99%
See 2 more Smart Citations
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).…”
Section: Researchgatementioning
confidence: 99%
“…edu, which is preferred by researchers in the social sciences and especially the humanities Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali et al, 2016;Matthews, 2016;Mikki et al, 2015;Nández & Borrego, 2013;Ortega, 2015;Thelwall & Kousha, 2015;Thelwall & Kousha, 2017;Van Noorden, 2014). Despite these disciplinary differences, however, ResearchGate is more heavily used by researchers overall than Academia.edu Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali et al, 2016;Laakso et al, 2017;Matthews, 2016;Meishar-Tal & Pieterse, 2017;Míguez-González et al, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017;Van Noorden, 2014). Use of ResearchGate is notably higher than that of Academia.edu among senior researchers Matthews, 2016;Mikki et al, 2015).…”
Section: Researchgatementioning
confidence: 99%
See 1 more Smart Citation
“…Academic social networks have been the subject of a fair amount of academic research, given their relatively recent entry into the scholarly communication landscape. A number of studies have been done on the adoption rates by researchers in a particular discipline (Muscanell & Utz, 2017;Marra, 2016;Ortega, 2015;Van Noorden, 2014;Haustein et al, 2014) or a particular country (Mikki, Zygmuntowska, Gjesdal, & Ruwehy, 2015;Campos & Valencia, 2015;Elsayed, 2015;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Meishar-Tal & Pieterse, 2017. Mikki et al (2015 found that ResearchGate was used most often by Norwegian scholars overall, though humanities scholars used Academia.edu more frequently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De la misma manera, Muscanell y Utz (2017) analizan el uso y los beneficios de ResearchGate en investigadores de Europa y Estados Unidos. Mientras que Míguez et al (2017) analizan estos aspectos en las Universidades de Portugal; y Araujo et al (2017) en el contexto de las comunidades científicas brasileñas y portuguesas. En el mismo orden de ideas, Jamali (2017) analiza si los miembros de ResearchGate, como autores de artículos de revistas cumplen con las políticas de derechos de autor de las editoriales.…”
Section: Introductionunclassified